The Relationship Between Serum Folic Acid Levels With The Cognitive Function of The Elderly - Hermanto, Hermanto; Muhartomo, Hexanto; Husni, Amin; Widiastuty, Maria Immaculata; Suryawati, Herlina; Wati, Arinta Puspita (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: Cognitive decline is a common condition that occurs in the elderly. One of the early indicators of senility is a decrease in cognitive function. Folic acid is thought to protect the arteries from damage because of homocysteine by converting homocysteine into cysteine and then excreted in the urine. Increased levels of homocysteine can interfere with vascular function and cause toxic effects on neurons thereby increasing the risk of cognitive decline. Objective: To determine the relationship between serum folic acid levels and cognitive function of the elderly. Method: Analytical descriptive research with a cross-sectional approach. The research subjects were the elderly who met the inclusion criteria and did not have exclusion criteria. The research was conducted from May to July 2022 at the Pucang Gading Nursing Home, Semarang. Serum folic acid levels were examined using the ELISA (Enzyme-linked immunosorbent assay) method. Cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA) simultaneously on the subject. Cognitive function is normal if the MoCA-INA value is ≥ 26 and it is said to be cognitive dysfunction if the MoCA-INA value is < 26. Data were analyzed using the Spearman test. Results are considered significant if the value of p <0.05.  Result: There is a strong positive correlation between serum folic acid levels and cognitive function in the elderly (r=0.914, p<0.001). There is a relationship between educational level and cognitive function (r=0.922, p<0.001) where higher education correlates with increased cognitive function in the elderly. Conclusion: There is a significant positive correlation between serum folic acid levels and cognitive function in the elderly